Ethical dimension of consuming frog components for medical and research purposes - Ahmad Zahari, Muhamad Syafiq; Darnis, Deny Susanti; Hashi, Abdurezak Abdulahi (IIUM Press, International Islamic University Malaysia, 2017)
Amphibians are known to possess a moist integumentary system which plays a vital role in its cutaneous respiration. In addition to this, its skin also possesses granular and mucus glands which secrete several potent bioactive compounds that enable them to protect themselves against predators and microbial infection. Recent development in technology have made it possible to extract certain compounds from amphibians which harboured a specific bioactivity characteristics such as antiviral, antibacterial, antifungal, antiprotozoal, antidiabetic, antineoplastic, analgesic and sleep inducing properties. Amphibian biology has provided us with an insight that could help mankind in treating various illness. Their immune defences are highly evolved by both innate and adaptive immune system. Therefore, this paper aims to discuss and elaborate on how Islam jurisdiction affects the rulings of frog components use for medical and research purposes.